2017
DOI: 10.1002/14651858.cd003079.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepines for psychosis-induced aggression or agitation

Abstract: The evidence from trials for the use of benzodiazepines alone is not good. There were relatively little good data and most trials are too small to highlight differences in either positive or negative effects. Adding a benzodiazepine to other drugs does not seem to confer clear advantage and has potential for adding unnecessary adverse effects. Sole use of older antipsychotics unaccompanied by anticholinergic drugs seems difficult to justify. Much more high quality research is needed in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
6

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 94 publications
0
48
0
6
Order By: Relevance
“…These studies mostly focus on the first day of treatment and include, for example, the use of short-acting olanzapine IM, short-acting aripiprazole IM, loxapine inhaled, sublingual asenapine and antihistamines. As a recent review towards medication for psychosis-induced aggression or agitation concluded there is only a small amount of evidence and of poor quality [39], future research could compare the effects of medications in emergency situations and long-term treatment. Finally, only studies with hostility scores as outcome measure are included and not the studies using physical violent incidents as an outcome measure, as there were too few of those.…”
Section: Discussionmentioning
confidence: 99%
“…These studies mostly focus on the first day of treatment and include, for example, the use of short-acting olanzapine IM, short-acting aripiprazole IM, loxapine inhaled, sublingual asenapine and antihistamines. As a recent review towards medication for psychosis-induced aggression or agitation concluded there is only a small amount of evidence and of poor quality [39], future research could compare the effects of medications in emergency situations and long-term treatment. Finally, only studies with hostility scores as outcome measure are included and not the studies using physical violent incidents as an outcome measure, as there were too few of those.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent Cochrane Database Review found little research evidence to support this common practice. 67 Comparing benzodiazepines to placebo found little difference on most outcome measures; adding benzodiazepines to antipsychotics did not further reduce agitation and aggression 4 hours after administration, and the combination of haloperidol and midazolam actually increased aggression 12 hours after administration. In an experimental paradigm that was designed to test aggressive responding during a competitive game, male subjects given diazepam were more likely to select higher shock levels for their opponents than those given placebo.…”
Section: Psychopharmalogical Interventionsmentioning
confidence: 97%
“…A recent Cochrane systematic review of the efficacy of BDZs in psychosis-induced aggression or agitation concluded that adding BDZs to other drugs does not appear to be clearly advantageous and increases the risk of unnecessary adverse effects. 78 Further, a recent meta-analysis 69 of 16 RCTs (for a total of 1,045 participants) investigating the efficacy of BDZ augmentation to antipsychotics in the treatment of schizophrenia found no evidence for use of this strategy.…”
Section: Resultsmentioning
confidence: 99%